Comparison of transverse facial venous sinus and jugular blood values in healthy and critically ill horses. (December 2013) - Hunter, B. G.; Schlipf, J. W.; Cebra, C.
Summary: Reasons for performing study: The transverse facial venous sinus (TFVS) can be used for blood collection in horses, but information on the validity of blood values from this site is limited. Objectives: To determine if packed cell volume (PCV), total solids (TS) and blood lactate concentrations in blood drawn simultaneously from a TFVS and jugular vein of critically ill horses are correlated and determine the effect of serial TFVS sampling on the same parameters in healthy horses. Study design: Prospective observational study. Methods: Critically ill horses had simultaneous blood samples drawn from a TFVS and jugular vein. Blood was also drawn from the left TFVS and jugular vein from 6 healthy, adult horses q. 6 h for 24 h, then q. 24 h for 72 h. Blood was drawn from the right TFVS and jugular vein q. 24 h for 96 h. All samples were analysed for PCV, TS and blood lactate concentration. Data were analysed with 2‐way repeated measures ANOVA. Significance was set at P≤0.05. Results: There were no significant differences in PCV, TS or blood lactate concentrations of TFVS samples compared with jugular blood in critically ill horses. Serial TFVS sampling in healthy horses had no significant effect on TS or blood lactate concentrations. Although PCV in the TFVS was significantly lower than in jugular blood on serial sampling, the difference was not considered clinically relevant. Conclusions: Packed cell volume, TS and blood lactate concentrations were comparable between the TFVS and jugular vein.